2006
DOI: 10.1016/j.jvs.2005.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous balloon occlusion of the inferior vena cava as an adjunct for treating ruptured type IV thoracoabdominal aneurysm and aortocaval fistula

Abstract: Spontaneous aortocaval fistulas are rare and thoracoabdominal aneurysms eroding into the inferior vena cava are rarer still. We describe a patient who presented to our hospital with a fistula between a Type IV thoracoabdominal aneurysm and the inferior vena cava. Expanding endovascular capabilities of vascular surgeons enabled us to insert proximal and distal occluding balloon catheters into the vena cava which greatly minimized blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Percutaneous balloon occlusion of the IVC to facilitate open surgical repair and minimize blood loss, as well as coil embolization of high output central fistulae, have been described. 24,25,28 In an attempt to circumvent the problems associated with open repair, endovascular stent-graft treatment has also been proposed to offer an attractive therapeutic alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous balloon occlusion of the IVC to facilitate open surgical repair and minimize blood loss, as well as coil embolization of high output central fistulae, have been described. 24,25,28 In an attempt to circumvent the problems associated with open repair, endovascular stent-graft treatment has also been proposed to offer an attractive therapeutic alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients undergoing an open repair had primary repair of the ACF from within the sac. Espinel et al 11 and Madani et al 46 used a retrograde balloon occlusion of the inferior vena cava (IVC) for venous control before primarily repairing the ACF. Four patients were repaired with a patch angioplasty of the IVC.…”
Section: Resultsmentioning
confidence: 99%
“…A literature review showed that this technique has only been documented in 1 case of a patient with a ruptured type IV thoracoabdominal aneurysm. 5 Here, the authors reported passing percutaneous balloons from both common femoral veins to obtain both distal and proximal control of the IVC, which minimized blood loss during repair. In retrospect, we could have similarly obtained proximal control of the IVC via a second balloon occluder.…”
Section: Discussionmentioning
confidence: 99%